Peran Guru PAI dalam Program Roots Day untuk Mengatasi Perundungan di Sekolah - Marwa, Khoirunnisa; Wahyuni, Ana Dwi (QuranicEdu: Journal of Islamic Education, 2024)
This research aims to identify the forms of bullying that occur in SMA Negeri 1 Karangmojo Gunungkidul, the school's efforts to prevent and overcome it, and analyze the role of Islamic Education (PAI) teachers in the Roots Day program. The researchers used a qualitative approach and data were collected through interviews, observations, and documentation. The research results showed that the level of bullying in the school was relatively low, but verbal bullying still occurred among students. One of the efforts made was through the Roots Day Anti-Bullying program. The role of PAI teachers in the Roots Day program is considered very effective in instilling positive values, building empathy, and preventing bullying. The efforts that have been made by the school are to implement the Roots Anti-Bullying program, put up anti-bullying posters in the school environment, and form a Violence Prevention and Handling Team (TPPK). The role of PAI teachers is at the forefront in character building and habituating students to behave positively towards others. The role of PAI teachers in this program is as a facilitator.